2020
DOI: 10.2147/cmar.s252232
|View full text |Cite
|
Sign up to set email alerts
|

<p>KLHL22 Regulates the EMT and Proliferation in Colorectal Cancer Cells in Part via the Wnt/β-Catenin Signaling Pathway</p>

Abstract: Background: Colorectal cancer (CRC) is one of the most common aggressive malignancies. KLHL22 functions as a tumor suppressor, and previous findings have demonstrated that KLHL22 can regulate the development of breast cancer and CRC. However, few studies have investigated the role of KLHL22 in CRC cell epithelial-to-mesenchymal transition (EMT) and proliferation. The current study aimed to detect the role of KLHL22 in CRC cell proliferation and EMT and to elucidate the probable molecular mechanisms through whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Overall, KLHL22 could be used as an independent prognostic factor to predict the overall and progression-free survival of patients with TNBC, as evidenced by our clinical data and expression studies. However, a study by Song et al ( 22 ) found that KLHL22 protein levels in clinicopathological tissue samples of patients were lower than those in normal tissues, and they further explained that KLHL22 acts as a tumor suppressor and regulates proliferation and epithelial-mesenchymal transition through the Wnt/β-catenin signaling pathway in colorectal cancer cells. In addition, Zhou et al ( 23 ) revealed that KLHL22 plays a crucial role in maintaining the programmed cell death protein 1 (PD-1) expression balance and preventing excessive suppression of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, KLHL22 could be used as an independent prognostic factor to predict the overall and progression-free survival of patients with TNBC, as evidenced by our clinical data and expression studies. However, a study by Song et al ( 22 ) found that KLHL22 protein levels in clinicopathological tissue samples of patients were lower than those in normal tissues, and they further explained that KLHL22 acts as a tumor suppressor and regulates proliferation and epithelial-mesenchymal transition through the Wnt/β-catenin signaling pathway in colorectal cancer cells. In addition, Zhou et al ( 23 ) revealed that KLHL22 plays a crucial role in maintaining the programmed cell death protein 1 (PD-1) expression balance and preventing excessive suppression of T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 86 Besides, KLHL22 can modulate the activity of GSK-3β to affect PI3K level via Wnt/β-catenin signaling pathway, further regulating the EMT process and cell proliferation in colorectal cancer. 87 A previous study has reported that KLHL22 can decrease the number of PD-1 located on the cell surface by promoting its ubiquitin degradation. Decreased KLHL22 contributes to the overaccumulation of PD-1, which inhibits the normal function of immune system and facilitates tumor development and progression.…”
Section: E3s In Regulation Of Pd-1/pd-l1 In Tumor Immunotherapymentioning
confidence: 98%
“…The kelch-like family member 22 ( KLHL22 ) is a tumour suppressor protein involved in the development/progression of several cancers [ 30 ]. Low expression of KLHL22 was found in CRC tissues.…”
Section: Canonical Wnt/β-catenin Pathway and Crcmentioning
confidence: 99%
“…KLHL22 overexpression was associated with decreased migration, invasion and reduced expression of the EMT markers, vimentin, N-cadherin, Twist1 and Snail1. Intriguingly, KLHL22 knockdown led to increased expression of β-catenin and LEF , while KLHL22 overexpression translates into GSK-3β upregulation and β-catenin downregulation [ 30 ] ( Table 1 ).…”
Section: Canonical Wnt/β-catenin Pathway and Crcmentioning
confidence: 99%